2018
DOI: 10.1002/cmdc.201700819
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated GluN2B Receptor Antagonists with a 3‐Benzazepine Scaffold Designed for PET Studies

Abstract: To analyze the N-methyl-d-aspartate (NMDA) receptor distribution in the central nervous system, fluorinated ligands that selectively address the ifenprodil binding site of GluN2B-subunit-containing NMDA receptors were developed. Various strategies to introduce a fluorine atom into the potent GluN2B ligand 2 (3-(4-phenylbutyl)-2,3,4,5-tetrahydro-1H-3-benzazepin-1,7-diol) were pursued, including replacement of the benzylic OH moiety with a fluorine atom (13) and introduction of fluoroethoxy moieties at various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The desired enantiomers of 3-benzazepin-1-ols 2-4 were synthesized from racemic secondary amine rac-1, [20] which was alkylated with 1-chloro-4-phenylbutane in the presence of tetrabutylammonium iodide (TBAI) to give rac-2.T he enantiomers (R)-2 and (S)-2 were separated by preparative chiral HPLC using the DaicelC hiralpak IA chiral column. Afterward, the benzyle thers of (R)-2 and (S)-2 werec leaved with H 2 and Pd/C to afford the phenols (R)-3 and (S)-3.F inally,t he enantiomerically pure phenols (R)-3 and (S)-3 were methylated with methyli odide to yield methyle thers (R)-4 and (S)-4 ( Figure 1).…”
Section: Synthesismentioning
confidence: 99%
“…The desired enantiomers of 3-benzazepin-1-ols 2-4 were synthesized from racemic secondary amine rac-1, [20] which was alkylated with 1-chloro-4-phenylbutane in the presence of tetrabutylammonium iodide (TBAI) to give rac-2.T he enantiomers (R)-2 and (S)-2 were separated by preparative chiral HPLC using the DaicelC hiralpak IA chiral column. Afterward, the benzyle thers of (R)-2 and (S)-2 werec leaved with H 2 and Pd/C to afford the phenols (R)-3 and (S)-3.F inally,t he enantiomerically pure phenols (R)-3 and (S)-3 were methylated with methyli odide to yield methyle thers (R)-4 and (S)-4 ( Figure 1).…”
Section: Synthesismentioning
confidence: 99%
“…Conversely, the specific binding values in the cerebellum were very low (21%-32% of total). The control binding of all 11 C-ligands to the forebrain regions were significantly reduced by coincubation with cold ligands, although no similar SCHEME 1 Synthesis of 11 Figure 2D-F). These results were similar to those of [ 3 H]CP-101,606, which is known to be a GluN2B subunit selective antagonist.…”
Section: In Vitro Studiesmentioning
confidence: 96%
“…7 Although these ligands showed an extremely high in vitro selectivity for the GluN2B subunit, none of them showed specific binding in vivo. [8][9][10][11] Claiborne et al reported N-(benzyl) amidine derivatives as orally efficacious GluN2B-selective NMDAR antagonists. 12 In addition, Curtis et al have reported that cinnamyl and 2-naphthyl analogs of benzyl amidine (CBA and NBA) have high-GluN2B selectivity, extremely high-binding affinity (the K i values of CBA, and NBA for [ 3 H] ifenprodil binding are 0.7 nM and 1.3 nM, respectively), and methoxy groups, which can be labeled with carbon-11.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations